2024
DOI: 10.1021/acsomega.4c01015
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformations of Peptides Containing the N-(2-Selenoethyl)glycine Moiety

Özge Pehlivan,
Kamil Wojtkowiak,
Aneta Jezierska
et al.

Abstract: The diselenide bond has attracted considerable attention due to its ability to undergo the metathesis reaction in response to visible light. In our previous study, we demonstrated visible-light-induced diselenide metathesis of selenocysteine-containing linear peptides, allowing for the convenient generation of peptide libraries. Here, we investigated the transformation of linear and cyclic peptides containing the N-(2selenoethyl)glycine moiety. The linear peptides were highly susceptible to the metathesis reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Based on this study, the authors further applied the metathesis reaction for the transformation of linear and cyclic peptides containing N -(2-selenoethyl)glycine moiety. 33 Payne et al reported the formation of asymmetric diselenide bonds between diselenide-linked protein dimer and diselenide-linked polyethylene glycol (PEG) dimer under non-reducing conditions, which was used for the functionalization of peptides and proteins via selenoether formation. 34 These studies suggest that peptides/proteins with diselenide bonds are not as stable as previously regarded.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this study, the authors further applied the metathesis reaction for the transformation of linear and cyclic peptides containing N -(2-selenoethyl)glycine moiety. 33 Payne et al reported the formation of asymmetric diselenide bonds between diselenide-linked protein dimer and diselenide-linked polyethylene glycol (PEG) dimer under non-reducing conditions, which was used for the functionalization of peptides and proteins via selenoether formation. 34 These studies suggest that peptides/proteins with diselenide bonds are not as stable as previously regarded.…”
Section: Introductionmentioning
confidence: 99%